SURFACE MODIFICATION OF FLY ASH FROM ASAM-ASAM COAL POWER PLANT USING STEARIC ACID AS HYDROPHOBIC INORGANIC MATERIAL - Manurung, Tety Wahyuningsih; Beladona, Siti Unvaresi Misonia; Hakim, Muh. Supwatul; Tesalonika, Lidya; Al-Hadi, Risfa Aliya; Iqbal, Rendy Muhamad (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
Abundant coal reserves make this material a substitute fuel choice, especially for industry. The use of coal carries a high risk due to incomplete combustion and produces fly ash products. Fly ash cause pollution and health risks as well as environmental contamination when they are released, deposited, or leached into the ecosystem over short or long periods of time. The high content of silica and alumina in fly ash can be utilized and modified into new materials with added value. This research aims to modify the surface of fly ash using stearic acid as a hydrophobic inorganic material. Fly ash from Asam-asam Coal Power Plant was characterized by using XRD and modified by immersing in stearic acid (2,4,6, and 8%) and 98% ethanol. The result showed that the contact angle increases when fly ash is modified on the surface using stearic acid. The contact angle increases with increasing stearic acid concentration. The highest contact angle was obtained at a stearic acid concentration of 8%, and the lowest at 2% was about 112.9 and 102.2, respectively. The fly ash composition was primarily silica and alumina, which were crystalline, as confirmed by XRD. These findings provide several aspects of fly ash and its potential as a candidate material for environmental remediation and waste management.